Knowledge, attitude, behaviour of the future healthcare professionals towards the self-medication practice with antibiotics - Tarek Benameur; Hassan Al-Bohassan; Abdullah Al-Aithan; Abdullah Al-Beladi; Hassan Al-Ali; Hassan Al-Omran; Neji Saidi (Journal of Infection in Developing Countries)
Introduction: Self-medication with antibiotics (SMA) is a major health problem in the developing world including the kingdom of Saudi Arabia (KSA). This practice remains an emerging challenge for the healthcare providers. A few previous studies have estimated the prevalence of SMA among the general population of KSA, but there had been no such studies on healthcare students.